Single Laser Shot Photoinduced Phase Transition of Rubidium Manganese Hexacyanoferrate Investigated by X‐ray Diffraction. Issue 27 (27th February 2019) - Azzolina, Giovanni; Collet, Eric; Mariette, Céline; Cammarata, Marco; Trzop, Elzbieta; Sander, Mathias; Levantino, Matteo; Nakagawa, Kosuke; Tokoro, Hiroko; Ohkoshi, Shin‐ichi; Bertoni, Roman
Abstract : We have studied by X‐ray diffraction the phase transition of microcrystals of rubidium manganese hexacyanoferrate, for which combined electron transfer and structural reorganization are responsible for a change of magnetic properties. The Rb0.94 Mn[Fe(CN)6 ]0.98 · 2.5H2 O system undergoes a phase transition between the tetragonal phase Fe II (S = 0)–CN–Mn III (S = 2) and the cubic Fe III (S = 1/2)–CN–Mn II (S = 5/2) phases. The thermal equilibrium phase transition shows a broad regime of bistability, responsible for the appearance of a thermal hysteresis in the approximate 185–300 K temperature range. We used a deposited film to study by X‐ray diffraction the switching from the tetragonal phase to the cubic phase, induced inside the thermal hysteresis by a single laser shot of tuneable power. Compared to previous measurements using local probes, our results show that the ns laser pulse induces a stable long‐range ordered cubic phase when conversion is partial or complete. Abstract : We have studied by X‐ray diffraction the phase transition of microcrystals of Rb0.94 Mn[Fe(CN)6 ]0.98 · 2.5H2 O, induced inside the thermal hysteresis by a single laser shot of tunable power. Our results show that a single ns laser pulse induces a stable long‐range ordered phase and that complete conversion can be reached.